Analysis Of the State of Automated Control Systems of Technological Processes at Substations - Xakimov Zafar Tulyaganovich; Rakhmatov Xudoyor Boboniyozovich; Olimbayev Otajon Azamat ugli (Zien Journals, 2021)
The management system is carried out without the participation of personnel, reducing labor costs, which contributes to saving on personnel
Keywords: Automated control system; substation; information processing; monitoring; control; quality